A Confirmatory Factor Analysis Model Of Academic Quality Management Of English Program Schools Under The Office Of The Basic Education Commission In Bangkok (Journal of Namibian Studies : History Politics Culture, 2024)
The objective of this research is to analyze the elements of the system of academic quality management of English program schools under Thailand’s OBEC in Bangkok. The samples are 18 school principals of English program schools under Thailand’s OBEC in Bangkok, 19 school deputy directors of academic department, 20 heads of English program department and 360 teachers of English program department or 417 samples in total, selected with the stratified sampling technique. The tool used in this research is a questionnaire with the reliability value of 0.958. The primary assumption for the Confirmatory Factor Analysis has the value of Kaiser Meyer-Olkin of 0.803, and the value from Bartlett's test of 2825.585, with the statistical significance level of 0.01. The outcomes from the CFA on the system of academic quality management of English program schools under Thailand’s OBEC in Bangkok show that the concurrence with the empirical data is as follows: χ2 = 1.77, p-value = 0.184, χ2/df = 1.77/1, GFI = 1.00, RMSEA = 0.043, AGFI = 0.97. The weights of the elements fall in the range of 0.44- 0.98, as follows: The weight of the element of curriculum development is 0.44, the weight of the element of teaching and learning management is 0.85, the weight of the element of educational measurement and evaluation is 0.98, the weight of the element of educational supervision is  0.71, the weight of the element of educational media, innovation, technology development is 0.80, the weight of the element of internal quality assurance system development is 0.93.